2013
DOI: 10.1111/j.2047-2927.2012.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

A guanidinylated bioreducible polymer as a novel gene carrier to the corpus cavernosum of mice with high‐cholesterol diet‐induced erectile dysfunction

Abstract: SUMMARYA prerequisite for the successful clinical application of gene therapy in erectile dysfunction (ED) is the availability of safe and efficient gene delivery systems. The aim of this study was to examine the effectiveness of guanidinylated bioreducible polymer (GBP) polyplexes for gene delivery systems, which take advantage of the biodegradability of reducible disulfide bonds and the cell-penetrating ability of guanidine groups. For in vitro transfection experiments, we used mouse cavernous endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…These results provide evidence that the relaxation effect of RCE is related to the inhibition of intracellular Ca 2+ increase. The rat VSMC line A7r5 is usually used for intracellular calcium homeostasis as a substitute smooth muscle cell for primary smooth muscle cells, such as human CSM cells [27,28]. We confirmed that increases of [Ca 2+ ] i evoked by 60 mM K + -containing solution in A7r5 cells were suppressed by RCE in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 72%
“…These results provide evidence that the relaxation effect of RCE is related to the inhibition of intracellular Ca 2+ increase. The rat VSMC line A7r5 is usually used for intracellular calcium homeostasis as a substitute smooth muscle cell for primary smooth muscle cells, such as human CSM cells [27,28]. We confirmed that increases of [Ca 2+ ] i evoked by 60 mM K + -containing solution in A7r5 cells were suppressed by RCE in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 72%